2022
DOI: 10.3390/molecules27144367
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydropyridines’ Stereoselective Formation, How Lockdown Assisted in the Identification of the Features of Its Mechanism

Abstract: The multicomponent reaction of aldehydes, cyano-containing C-H acids, esters of 3-oxocarboxylic acid and ammonium acetate led to unexpected results. The boiling of starting materials in methanol for one to two hours resulted in the formation of polysubstituted 1,4,5,6-tetrahydropyridines with two or three stereogenic centers. During the 2020 lockdown, we obtained key intermediates of this six-step domino reaction. A number of fast and slow reactions occurred during the prolonged stirring of the reaction mass a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…47 A detailed study of the mechanism have showed that this reaction proceeds through the formation of substituted 2-hydroxypiperidines (non-fluorinated analogues of 3) followed by dehydration to 3,4,5,6-tetrahydropyridines and slow isomerization at rt to 1,4,5,6-tetrahydropyridines. 50 Acidification of the reaction media also promoted isomerization.…”
Section: Methodsmentioning
confidence: 99%
“…47 A detailed study of the mechanism have showed that this reaction proceeds through the formation of substituted 2-hydroxypiperidines (non-fluorinated analogues of 3) followed by dehydration to 3,4,5,6-tetrahydropyridines and slow isomerization at rt to 1,4,5,6-tetrahydropyridines. 50 Acidification of the reaction media also promoted isomerization.…”
Section: Methodsmentioning
confidence: 99%